Various causative factors and associated complications of childhood obesity in Jeddah, western region, Saudi Arabia: Jeddah, western region, Saudi Arabia. - Al-Agha, Abdulmoein; Ragbi, Rahaf; Mabkhoot, Yusra; Bahwirith, Ashjan; Mohammed, Arwa; Alhabi, Elham; Dumyati, Bashayer; Milyani, Asmaa Adel (Acta Biomedica Atenei Parmensis, 2020)
objective: to investigate the causative factors and complications attributable to obesity in children living in jeddah, saudi arabia. methods: this is a retrospective study encompassing a sample size of 151 children and adolescents between the ages of 4 and 20 years. data was collectived through revieweing medical records, medical files on the hospital electironic system and clinical interviews conducted with legal guardians. date of study was from january to june 2018, and was carried in jeddah, western region, saudi arabia. results: data was entered, coded, cleaned and analysed using statistical package for social science (IBM SPSS), version 22. the analysis was done by assessing the significance of various risk factors ands equalae in their contribution to paediatric obesity by one way ANOVA for nominal variables of more than two categories and independent sample t-test for the nominal variables with two categories. the sample was 47% of the male gender whereas females made for the remaining 53%. the causation of obesity was distributed among the following factors: an unhealthy diet, a sedentary lifestyle, medications such as glucocorticoids, and complications attributed to obesity included gastro-oesophageal reflux, hypertension, precocious puberty, sleep apnoea, psychological disturbances and fatty liver diseases. conclusion: environmental factors were found to be the most predominant cause, where the majority of children were found to be leading a sedentary lifestyle, following an unhealthy diet, and skipping meals. the msot recurring complications involved psychosocial and behavioural abnormalities, and among the medical consequences, gastro-oesophageal reflux and obstructive sleep apnoea were the most prevalent.